Preliminary Study of pH Sensor for Engine Oil Deterioration Detection Using Anodized Ta2O5 Nanotubular - Ngadiman, Nur Lili Suraya; Abdul Rani, Rozina; Zulkifli, Zulasyraf Farhan; Abdullah, Muhamad Firdaus; Makhsin, Siti Rabizah; Zolkapli, Maizatul; Zoolfakar, Ahmad Sabirin; Nour, Majid (International Journal of Integrated Engineering, 2022)
pH sensor is one of the sensing principles that can be employed in detection of engine oil deterioration. To avoid unnecessary changing of engine oil while maintaining the oil quality consumed by car’s engine, engine oil deterioration sensor is required to continuously monitor the oil condition. In this work, we fabricated pH sensor sensing layer made up of tantalum thin film. Ta2O5 nanotubular was constructed as the medium of interaction to measure the quality of engine oil. Anodization synthesis method was used to fabricate the sensing layer by varying the anodization time. Two samples anodized at 30 min and 60 min were tested in pH buffer solution at pH ranging from 2, 4, 7, 10 and 12. Further characterization using field emission scanning electron microscope (FESEM) was conducted to investigate the surface morphology properties, while X-ray diffraction (XRD) was conducted to obtain crystal properties of Ta2O5 nanotubular. A homogeneous Ta2O5 nanostructures with cubic crystal structure and pore diameter ranging between 15 to 20 nm was obtained. 30 min sample tested in pH buffer solution has better adsorption of H+ ions with linear pH sensitivity of 31.616 mV/pH and good stability. Therefore, anodization method can be an alternative to fabricate pH sensor for oil deterioration detection system. Additionally, other study on chemical sensor for the detection of engine oil deterioration level are also discussed in this paper.